Structural and functional insights into the pilotin-secretin complex of the type II secretion system. - Shuang Gu; Saima Rehman; Xiaohui Wang; Vladimir E Shevchik; Richard W Pickersgill (PLoS Pathogens)
Gram-negative bacteria secrete virulence factors and assemble fibre structures on their cell surface using specialized secretion systems. Three of these, T2SS, T3SS and T4PS, are characterized by large outer membrane channels formed by proteins called secretins. Usually, a cognate lipoprotein pilot is essential for the assembly of the secretin in the outer membrane. The structures of the pilotins of the T3SS and T4PS have been described. However in the T2SS, the molecular mechanism of this process is poorly understood and its structural basis is unknown. Here we report the crystal structure of the pilotin of the T2SS that comprises an arrangement of four α-helices profoundly different from previously solved pilotins from the T3SS and T4P and known four α-helix bundles. The architecture can be described as the insertion of one α-helical hairpin into a second open α-helical hairpin with bent final helix. NMR, CD and fluorescence spectroscopy show that the pilotin binds tightly to 18 residues close to the C-terminus of the secretin. These residues, unstructured before binding to the pilotin, become helical on binding. Data collected from crystals of the complex suggests how the secretin peptide binds to the pilotin and further experiments confirm the importance of these C-terminal residues in vivo.